پەیوەندی سکیسییەکان لەگەڵ ماد و پارسەکان (٧١٤-٣٣٠ پ.ز) (موستەل) - اسماعيل, صلاح كانبى; حسین, سه‌میر حسن (Sulaimani Journal for Humanities, 2022)
The race was among the great nomadic tribes, and they played an important role in the events and changes of the first millennium BC, because of their migration, they occupied a large area of North Asia, southern Siberia, the North Sea and behind the Caucasus Mountains. Their conquests of Western Asia led to a violent conflict between the forces of that time and the Scythians. The consequences of this conflict left a long-term impact on the region and even the arrival of the wave of these tribes led to the destruction of many powerful forces of the time. One of the most important characteristics of these tribes is their relationship with their contemporaries, both as the main force in power, and as mercenaries and fighting forces. In this paper, based on the descriptive historical method, the events and developments of the emergence and relationship of the Scythians with the Medes and Persians are discussed chronologically within three axes: The first topic is a summary of the Scythians, the second topic focuses on the relationship between the Scythians and the Medes, and the last topic discusses the relationship between the Scythians and the Persians and the effects of this relationship.